2021
DOI: 10.1177/1066480720986496
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: Boredom in the Family

Abstract: This research is focused on the subject of boredom in the families during the stay-at-home process forced by coronavirus disease 2019 pandemic. The literature on boredom was reviewed, and then the qualitative research was designed with the open-ended questions appropriate for the subject and purpose. The research was conducted between April 20 and 29, 2020, in Istanbul, Turkey, with the participation of 264 families. The most significant findings of the research showed that family members accustomed to active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…Findings of the same study suggested that family members were feeling relatively less close to their children and the difference was significant. Although Latif & Karaman (2021) reported in their study that staying at home increased boredom and led people to information technologies and unintentional behaviors such as excessive eating, they also concluded that there was no conflict among the family members and this process taught them to be patient and strong. Sari et al, (2021) found that harsher behaviors by parents toward their children during the pandemic process were significant and relatively higher compared to the pre-pandemic period.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Findings of the same study suggested that family members were feeling relatively less close to their children and the difference was significant. Although Latif & Karaman (2021) reported in their study that staying at home increased boredom and led people to information technologies and unintentional behaviors such as excessive eating, they also concluded that there was no conflict among the family members and this process taught them to be patient and strong. Sari et al, (2021) found that harsher behaviors by parents toward their children during the pandemic process were significant and relatively higher compared to the pre-pandemic period.…”
Section: Discussionmentioning
confidence: 95%
“…According to their study results, it was determined, like the present study, that parents displayed negative attitudes such as conflict, stress, irritability, and harsh behavior. When the time of the study and its sample group were analyzed, it is considered that the difference in the study of Latif & Karaman (2021) stemmed from the fact that their study was conducted during the first months of the pandemic, and this might have had different effects on parents. Moreover, this study covered the 3-week full lockdown period.…”
Section: Discussionmentioning
confidence: 99%
“…Codzienne nawyki, nawet tak nielubiane jak chodzenie do szkoły, dają poczucie bezpieczeństwa, które zostało zachwiane. Dzieci, dla których podstawową relacją społeczną jest ta między nimi a rodzicami nierzadko skonfrontowane zostały z przemęczonymi, zestresowanymi rodzicami, którzy albo tracili pracę, albo usiłowali pracować zdalnie, albo pracowali stacjonarnie przy coraz wyższym ryzyku zarażenia (Cooper, Thomas and Bamishigbin, 2021;Latif and Karaman, 2021). Nastolatki, dla których podstawowymi relacjami są te rówieśnicze, zostały odcięte od zwyczajnych kontaktów, ograniczone do komunikacji online.…”
Section: Pandemia I Edukacjaunclassified